Abstinência de álcool e sobrevida na hepatite alcóolica no Hospital de Base de São José do Rio Preto - Rocha, Márcia Fumie da (2018)
Alcoholism is a dependence syndrome with behavioral cognitive and physiological phenomena developed due to repetitive consumption of alcohol. Among the various harmful effects of alcohol, alcoholic hepatitis (AH) is a syndrome of inflammation of the liver in people who consume excessive amounts of ethanol, with important repercussions for the patient, leading to death in more severe cases. An alcohol abstinence has been considered an independent predictor of long term-survival. Aim: analyzing survival rate and associated alcohol abstinence factors in patients admitted for AH, at a college hospital. Method: A medical report retrospective analysis of all AH patients enrolled during a period 29 months (02/2011 – 06/2013) has been carried out. Patients’ demographic, clinical and laboratory data have been collected, as well as their quantification of alcohol abuse, abstinence period, date of the last clinical follow-up or death. Results: from the 1105 hospital admissions, 100 patients have been included in the study. Male and white were predominant. Hepatic cirrhosis has been found in 86% of the sample, and its most common decompensation has been ascites. Through prognostic scores for AH, the following results have been observed MELD (Model for End Stage Liver Disease) 20 (6 - 40), MELD - Na 24 (6 - 40), Maddrey discriminant function (DF) 40 (± 27.3), Glasgow 8 (5 - 12) and ABIC (Age, Bilirubin, INR and Creatinine) 7.29 (4.40-10.53). The sample overall death rate has been 64%. Infections have occurred in 53% of the patients. The overall rate of the sample was 64%. Regarding abstinence, data have been available for 55 patients of the studied sample, and it has occurred in 15 (27.3%) of them. Through a univariate analysis, alcohol abstinence (P<0.001), DF (P <0.001), acute renal injury (AKI) (P <0.001), MELD (P <0.001), MELD - Na (P <0.001), Glasgow (P <0.001), ABIC (P= 0.001) and infection (P = 0.004) were variables have been associated with survival. Through a multivariate analysis, only alcohol abstinence (P = 0.006), DF<32 (P = 0.001) and absence of AKI (P = 0.001) have been remained predictors of survival. Conclusions: The rate of alcohol abstinence after discharge was low, and the patient’s own decision, psychological and family support the main tools have been associated with their adherence. A long-term survival has been shown predicted by the following factors: alcohol abstinence, DF <32 and the absence of AKI.